Alpha-1-Antitrypsin Deficiency: Disease Management and Learning from Studies. (15th March 2017) - Greulich, Timm
ABSTRACT: Alpha-1-antitrypsin deficiency (AATD) is one of the most frequent genetic causes of liver and lung diseases. Despite its known association with chronic obstructive pulmonary disease (COPD), AATD is largely unrecognised and underdiagnosed. Cases of AATD exist within every COPD or spirometry population but must be actively investigated. AATD is a laboratory diagnosis that must be confirmed by a blood test. A number of clinical 'clues' can raise suspicion of AATD, potentially facilitating earlier diagnosis and initiation of appropriate treatment. Alpha-1-antitrypsin augmentation therapy has a clear role in patients with severe AATD and a FEV1 ≤65% predicted. Emerging evidence suggests that attenuating the decline in lung density may prolong the time to respiratory failure.